Different determinants affecting first mover advantage and late mover advantage in a smartphone market: a comparative analysis of Apple iPhone and Samsung Galaxy. Issue 3 (4th March 2022) - Park, Changhyun
ABSTRACT: Entry timing is critical for a firm's sustainability, and it is determined after comparing the first mover advantage (FMA) and the late mover advantage (LMA). This study aims to continue the extant discussion on FMA and LMA to explore the important determinants and their effects on FMA or LMA in a smartphone market. The methodology of building a theory from a comparative case study is adopted using Apple iPhone and Samsung Galaxy cases in a smartphone market. This study verified that market- and firm-level determinants are more linked with FMA, and the isolating mechanism along with the environment as well as firm-level enablers are useful for explaining FMA. This study also uniquely found that the product-level determinant is closely linked with LMA, which has not been explored much in relation to LMA. This study theoretically contributed to extending the conceptual framework as well as enabling the mechanism of entry advantage, and it has managerial implications of how the first mover or the late mover can benefit from their entry advantage by exploiting their relative strength.